Arabidopsis B‐box transcription factors BBX20‐22 promote UVR8 photoreceptor‐mediated UV‐B responses. (27th May 2022) - Podolec, Roman; Wagnon, Timothée B.; Leonardelli, Manuela; Johansson, Henrik; Ulm, Roman
SUMMARY: Plants undergo photomorphogenic development in the presence of light. Photomorphogenesis is repressed by the E3 ubiquitin ligase CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1), which binds to substrates through their valine–proline (VP) motifs. The UV RESISTANCE LOCUS 8 (UVR8) photoreceptor senses UV‐B and inhibits COP1 through the cooperative binding of its own VP motif and photosensing core to COP1, thereby preventing COP1 binding to substrates, including the basic leucine zipper (bZIP) transcriptional regulator ELONGATED HYPOCOTYL 5 (HY5). As a key promoter of visible light and UV‐B photomorphogenesis, HY5 requires coregulators for its function. The B‐box family transcription factors BBX20–BBX22 were recently described as HY5 rate‐limiting coactivators under red light, but their role in UVR8 signaling was unknown. Here we describe a hypermorphic bbx21‐3D mutant with enhanced photomorphogenesis, carrying a proline‐to‐leucine mutation at position 314 in the VP motif that impairs the interaction with and regulation by COP1. We show that BBX21 and BBX22 are UVR8‐dependently stabilized after UV‐B exposure, which is counteracted by a repressor induced by HY5/BBX activity. bbx20 bbx21 bbx22 mutants under UV‐B are impaired in hypocotyl growth inhibition, photoprotective pigment accumulation and the expression of several HY5‐dependent genes under continuous UV‐B, but the immediate induction of marker genes after exposure to UV‐B remains surprisingly rather unaffected. We conclude that BBX20–BBX22 contribute to HY5 activity in a subset of UV‐B responses, but that additional, presently unknown, coactivators for HY5 are functional in early UVR8 signaling. Significance Statement: A subfamily of B‐box transcription factors promotes plant responses to visible light. In this work, we describe a hypermorphic bbx21 mutant with enhanced photomorphogenesis, and we show that BBX proteins are involved in HY5‐dependent, UVR8 photoreceptor‐mediated responses to UV‐B. BBX21 and BBX22 are stabilized under UV‐B, their stability is fine‐tuned through a HY5‐dependent feedback loop and they promote the expression of phenylpropanoid biosynthesis genes under continuous UV‐B, but apparently not the acute induction of those genes.